Pelaksanaan Rehabilitasi Terhadap Pecandu Narkoba di Kota Ambon - Amrin, Andi; Toule, Elsa Rina Maya; Adam, Sherly (Postgraduate Program in Law, Universitas Pattimura, 2023)
Introduction: The implementation of rehabilitation for drug addicts in the city of Ambon is not yet in accordance with what is mandated by law.Purposes of the Research: This study also aims to analyze and discuss the implementation of rehabilitation for narcotics addicts in the city of Ambon in accordance with Law No. 35 of 2009 and to analyze and discuss the obstacles faced in the implementation of rehabilitation for narcotics addicts in Ambon City.Methods of the Research: The type of research used is normative juridical research using a statute approach, a conceptual approach, and a case approach. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials.Results of the Research: Although the implementation of rehabilitation is a recommendation by the Assessment Team to victims of drug abuse and drug addicts to carry out medical rehabilitation and social rehabilitation, all stages such as the stage of medical rehabilitation (Detoxification), the non-medical rehabilitation stage and the further development stage have not been carried out properly. Apart from that, the process of implementing rehabilitation for drug addicts is only carried out through outpatient treatment while inpatient treatment is never carried out so that the guarantee for narcotics addicts to receive medical rehabilitation and social rehabilitation in accordance with the mandate and objectives of drugs in the Law cannot be fulfilled properly. Obstacles in implementing rehabilitation for drug addicts in the city of Ambon include: The law or the law itself does not clearly regulate the availability of facilities (rehabilitation centers or places) and infrastructure (financial) to support the implementation of rehabilitation and there is still a lack of medical personnel and staff. - specialist staff to support the implementation of social rehabilitation and medical rehabilitation